Carbon monoxide‐releasing molecule‐3 (CORM‐3) offers protection in an in vitro model of compartment syndrome. (19th July 2019) - Bihari, Aurelia; Chung, Kyukwang (Akira); Cepinskas, Gediminas; Sanders, David; Schemitsch, Emil; Lawendy, Abdel‐Rahman
Abstract: Objective: Limb compartment syndrome (CS), a complication of trauma, results in muscle necrosis and cell death; ischemia and inflammation contribute to microvascular dysfunction and parenchymal injury. Carbon monoxide‐releasing molecule‐3 (CORM‐3) has been shown to protect microvascular perfusion and reduce inflammation in animal models of CS. The purpose of the study was to test the effect of CORM‐3 in human in vitro CS model, allowing exploration of the mechanism(s) of CO protection and potential development of pharmacologic treatment. Methods: Confluent human vascular endothelial cells (HUVECs) were stimulated for 6 h with serum isolated from patients with CS. Intracellular oxidative stress (production of reactive oxygen species (ROS)) apoptosis, transendothelial resistance (TEER), polymorphonuclear leukocyte (PMN) activation and transmigration across the monolayer in response to the CS stimulus were assessed. All experiments were performed in the presence of CORM‐3 (100 μM) or its inactive form, iCORM‐3. Results: CS serum induced a significant increase in ROS, apoptosis and endothelial monolayer breakdown; it also increased PMN superoxide production, leukocyte rolling and adhesion/transmigration. CORM‐3 completely prevented CS‐induced ROS production, apoptosis, PMN adhesion, rolling and transmigration, while improving monolayer integrity. Conclusion: CORM‐3 offers potent anti‐oxidant and anti‐inflammatory effects, and may have a potential application to patients at risk of developing CS.